2011
DOI: 10.2298/fupct1101009i
|View full text |Cite
|
Sign up to set email alerts
|

Allicin and related compounds: Biosynthesis, synthesis and pharmacological activity

Abstract: In this review, the biosynthesis of allicin (allyl thiosulfinate) by enzymatic transformation of alliin and various methods of its synthesis with detailed investigation of mechanisms and kinetics are summarized. A convenient method is also described for determination of allicin stability and the utility of the inclusion complexes of this pharmacologically active agent with β-cyclodextrins in increasing its stability. Allicin is the initial precursor for the production of ajoene ((E)- and (Z)-4,5,9-trith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
47
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 38 publications
2
47
0
5
Order By: Relevance
“…Previous research demonstrated that garlic may be effective against cardiovascular disease because of its antithrombotic, hypolipidemic, hypocholesterolemic, antihypertensive, antidiabetic, and antihyperhomocysteinemia effects (14,15). Further, garlic possesses many other biological activities, including antimicrobial, antioxidant, anticancer, antimutagenic, antiasthmatic, and anti-inflammatory immune modulation activities and prebiotic activities (14)(15)(16)(17)(18)(19)(20)(21)(22). Evidence suggests that the biological and medical functions of garlic are mainly due to its high level of organosulfur compounds (15), while proteins derived from garlic do not have antimicrobial activity (23) and phenolic compounds make only a minor contribution (24).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Previous research demonstrated that garlic may be effective against cardiovascular disease because of its antithrombotic, hypolipidemic, hypocholesterolemic, antihypertensive, antidiabetic, and antihyperhomocysteinemia effects (14,15). Further, garlic possesses many other biological activities, including antimicrobial, antioxidant, anticancer, antimutagenic, antiasthmatic, and anti-inflammatory immune modulation activities and prebiotic activities (14)(15)(16)(17)(18)(19)(20)(21)(22). Evidence suggests that the biological and medical functions of garlic are mainly due to its high level of organosulfur compounds (15), while proteins derived from garlic do not have antimicrobial activity (23) and phenolic compounds make only a minor contribution (24).…”
mentioning
confidence: 99%
“…The primary sulfur-containing constituents in garlic are S-alk-(en)yl-L-cysteine sulfoxides, such as alliin [(ϩ)-(S)-allyl-L-cysteine-sulfoxide] and ␥-glutamyl cysteines (15,16). When a raw garlic bulb is crushed, alliin and alliinase, which are stored in sep-arate cellular compartments of the garlic clove, are mixed together.…”
mentioning
confidence: 99%
See 3 more Smart Citations